EVALUASI HASIL PELATIHAN REFRESHING PENYULUH LAPANGAN KELUARGA BERENCANA - Suhartina, Suhartina; Heriyanto, Meyzi; Kiswanto, Kiswanto (Jurnal Ilmu Administrasi Negara, 2019)
Evaluation of Results of Refreshing Training for Family Planning Field Planning. The purpose of this study was to find out the refreshing training of family planning extension officers of the BKKBN Representative Office of Riau Province in 2017. This study used a quantitative descriptive approach. The study population was all trainees totaling 100 people. Primary data is obtained directly by using questionnaires, interviews, observation and documentation. Data were analyzed using descriptive statistical methods based on Likert scale. The results showed that every indicator in the refreshing training program at the Family Planning Field Extension Workers (PLKB) Representative Office of the BKKBN of Riau Province in 2017 was good and quite good. Resource persons’ activities in refreshing training were good enough, with the average response rate of respondents 3.39. Motivation of participants to take refreshing training is good.